Production bio-Fertilizer, organic compost and biogas for smallholder agriculture - Silva Júnior, Francisco José da; Monteiro, Maria Kalyane Duarte; Vieira, Allan Sarmento; Ventura, Ana Flávia Albuquerque; Ventura Júnior, Raul (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper proposes the development of a portable digester that uses recyclable materials in their composition, and which aims to minimize the costs of implementation for small rural producers and consequently help in preserving the environment, reducing carbon gas emissions under the Kyoto Protocol. Despite being a technology quite widespread in southern Brazil, the models proposed in the literature, still have high costs at the facility, making it infeasible to your installation to family agriculture. Is notorious, that investments in technology are needed, since the benefits to increase social equity and environmental quality. Innovation is to propose a biodigester that uses recyclable materials in its structure and can be moved to any location of the country estate. With this bio-digester at hand, will be carried out a survey of technology, in order to ascertain its effective to suit the reality of Paraibano and the benefits generated for family farming. Next you’ll be using a methane gas detection equipment, in order to follow the evolution of it. The result shows a quite versatile, inexpensive and very useful for family farming. However the biodigestor proposed is a product essential in improving the quality of life of the local community, since they propose to generate extra income, maximizing social equity and minimizing the negative impacts on nature.